1969
DOI: 10.1107/s0567740869003979
|View full text |Cite
|
Sign up to set email alerts
|

X-ray studies of C25 terpenoids. III. The crystal structure of ceroplastol I p-bromobenzoate

Abstract: The structure of ceroplastol I, C25H400, a C25 terpenoid isolated from an insect wax, has been determined by X-ray analysis of its heavy atom derivative, ceroplastol I p-bromobenzoate. Crystals of the p-bromobenzoate are orthorhombic, space group P212121 with four molecules contained in the unit cell of dimensions, a= 18.67, b= 21.74, c= 7.02 ~. The crystal structure was solved by means of threedimensional Fourier syntheses using the heavy atom technique. The atomic parameters were refined by block-matrix leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…var subisidiosa Asah. To date several sesterterpenes have been reported including: ophiobolins A (Nozoe et al, 1965;Morisaki, Nozoe & Iitaka, 1968), B and C (Nozoe, Hirai & Tsuda, 1966), D (Itai, Nozoe, Okuda & litaka, 1969), ceroplastol I (Iitaka, Watanabe, Harrison & Harrison, 1969), cheilanthatriol (Khan, Zaman, Chetty, Gupta & Dev, 1971) and fusicoccin (Ballio et al, 1968;Hough, Hursthouse, Neidle & Rogers, 1968;Barrow, Barton, Chain, Ohnsorge & Thomas, 1971;it has not yet been confirmed that fusicoccin really is a sesterterpene). The same compound was also found in the lichens of L. retigera group collected in the western Himalayas (Rao, Sarma & Seshadri, 1965.…”
Section: Introductionmentioning
confidence: 99%
“…var subisidiosa Asah. To date several sesterterpenes have been reported including: ophiobolins A (Nozoe et al, 1965;Morisaki, Nozoe & Iitaka, 1968), B and C (Nozoe, Hirai & Tsuda, 1966), D (Itai, Nozoe, Okuda & litaka, 1969), ceroplastol I (Iitaka, Watanabe, Harrison & Harrison, 1969), cheilanthatriol (Khan, Zaman, Chetty, Gupta & Dev, 1971) and fusicoccin (Ballio et al, 1968;Hough, Hursthouse, Neidle & Rogers, 1968;Barrow, Barton, Chain, Ohnsorge & Thomas, 1971;it has not yet been confirmed that fusicoccin really is a sesterterpene). The same compound was also found in the lichens of L. retigera group collected in the western Himalayas (Rao, Sarma & Seshadri, 1965.…”
Section: Introductionmentioning
confidence: 99%
“…The C (4)-Br bond length is normal for this type of bond in p-bromophenyl derivatives [1.870 (6) Belew, 1979;Iitaka, Watanabe, Harrison & Harrison, 1969;Py~alska, Py~;alski & Borowiak, 1980;Kaftory, 1979;Destro, 1979;Liu & Davis, 1980;Bryan, Hartley, Peckler, Fujita, Nagao & SenD, 1980]. The C(1)-C(7) distance is shorter than expected for a C(spE)-C(sp 3) bond, but the C(7)-S distance is significantly longer than the C(methylene)-S single bond found in sulfoxides, for example: 1.802(2) (Svinning, Mo & Bruun, 1976), 1.813 (2) (HoyosGuerrero, Martinez-Carrera & Garcia-Blanco, 1983), 1.815 (8) (Koziot, Ksi¢~opolski & Janczewski, 1983), 1.817 (4)/k (Tranqui, Richard, Vicat & Fillion, 1974).…”
mentioning
confidence: 99%